Formulasi dan Evaluasi Ekstrak Aseton Kulit Putih Semangka Merah Non Biji (Citrullus Vulgaris S) dengan Niacinamide sebagai Gel Pelembab Kulit dengan Uji Kelembapan - Anis Priani; Ade Irawan; Teguh Adiyas Putra (Syntax Corporation Indonesia, 2024)
This research was carried out with the aim of identifying the content of phytochemical compounds of alkaloids, flavonoids, tannins and saponins in the acetone extract of seedless red watermelon rind (Citrullus vulgaris), knowing the results of evaluating the physical properties of the acetone extract gel of seedless red watermelon rind (Citrullus vulgaris) with niacinamide against various concentrations of moisturizing gel preparations, and comparing the best moisture test concentration on acetone extract gel preparations of seedless red watermelon rind (Citrullus vulgaris) in providing optimal results. This research is a laboratory study of the experimental formulation of acetone extract of seedless red watermelon rind (Citrullus vulgaris) to determine the formulation and concentration of the best extract produced. The research results showed that acetone extract from the white skin of red seedless watermelon (Citrullus vulgaris) contained phytochemical compounds alkaloids, flavonoids, and polyphenol as well as lycopene in the white skin of red seedless watermelon (Citrullus vulgaris). The results of the evaluation of the physical properties of the acetone extract gel of seedless red watermelon rind (Citrullus vulgaris) in the negative control, 2.5% concentration, 5% concentration, and 7.5% concentration met the test requirements but did not meet the spreadability test requirements. And the best concentration of water content test in the acetone extract gel preparation of seedless red watermelon rind (Citrullus vulgaris) in providing optimal results is found in the gel preparation with a concentration of 7.5%.